A hybrid sodium ion battery positive electrode material and preparation method thereof
By combining O3 and P2 layered sodium metal oxides in the positive electrode material of sodium ion battery and adopting specific process treatment, the problem of poor stability of the positive electrode material when exposed to air is solved, and higher stability and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202211734222.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The existing sodium ion battery positive electrode materials have poor stability when exposed to air, and the surface residual alkali growth is high, affecting the electrochemical performance.
The positive electrode material of mixed sodium ion battery, including O3-type layered sodium metal oxide and O3-type layered sodium metal oxide coated with the surface of O3-type layered sodium metal oxide, is used to improve the stability and electrochemical properties of the material through specific calcination and shelving treatment processes.
It effectively reduces the residual alkali content of the positive electrode material when exposed to air, improves the stability and circulation performance of the material, and maintains a high discharge specific capacity.
Smart Images

Figure CN116014119B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a hybrid sodium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] Although lithium-ion batteries have been widely used in fields such as electric vehicles, they also face some thorny problems that are difficult to completely solve in the short term. For example, in addition to normal charging and discharging reactions, lithium-ion batteries also have many side reactions; lithium resources are distributed in a low content in the earth's crust, and as the usage increases year by year, their price is getting higher and higher, while sodium resources are widely distributed in the earth's crust and are easy to obtain, so the cost of sodium resources is relatively low.
[0003] Sodium-ion batteries have a similar working principle to lithium-ion batteries. Sodium-ion batteries are an important component of low-cost and high-safety energy storage facilities. The development of stable sodium-ion battery positive electrode materials is an urgent problem to be solved.
[0004] Layered oxide sodium ion battery positive electrode materials can be generally divided into two types, P2 and O3, according to different atomic arrangements. P2 type positive electrode materials usually have low capacity due to the low content of Na ions in the material, but the material has good cycle stability, while O3 type positive electrode materials can generally provide higher specific capacity due to their high Na content, but due to the Na-H exchange, the Na element in the material is easy to react with water and carbon dioxide in the air, resulting in poor material stability. For example, Chinese patent document CN114744179A provides a sodium ion battery positive electrode material and a preparation method thereof, and the ion battery positive electrode material provided is O3 type layered sodium oxide, which combines ultrasonic dispersion and wet grinding mixing methods, and a calcination system combined with annealing is used to improve the uniformity of the sodium ion battery positive electrode material, but the positive electrode material is easy to precipitate sodium when placed in the air, resulting in the growth of residual alkali on the surface, affecting the electrochemical properties of the material.
[0005] Chinese patent document CN115148984A discloses an O3-P2 composite phase sodium ion positive electrode material, which includes an O3-type oxide layer and a P2-type oxide layer. The structural formula of the O3-P2 composite phase sodium ion positive electrode material is NaxMO2, 0.8≤X≤1, M includes at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Li, Ta, La, Nb, Zr, Mg, Al, Sn, Ru, Sr, W, Mo, B, and F; the P2-type oxide layer is in situ generated on the surface of the O3-type oxide layer to form a core-shell structure. It has excellent charge and discharge specific capacity, excellent cycle performance, low surface residual alkali content, and excellent comprehensive performance of the material. However, this method requires step-by-step temperature calcination, and after calcination, the material needs to be cooled by an ultra-fast cooling process to achieve the purpose of reducing the residual alkali content on the surface of the material, and annealing treatment is also required, and the process is complicated. In addition, after the material is exposed to the air, the growth rate of residual alkali in the material is too high, and the stability of air exposure is poor. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the positive electrode material in the prior art, such as high residual alkali and poor stability when exposed to air, thereby providing a hybrid sodium ion battery positive electrode material and a preparation method thereof.
[0007] The present invention provides a hybrid sodium ion battery positive electrode material, comprising an O3-type layered sodium metal oxide and a P2-type layered sodium metal oxide coated on the surface of the O3-type layered sodium metal oxide;
[0008] Wherein, the chemical formula of O3 type layered sodium metal oxide is: NaxNiaFebMncO2, 0.2≤a≤0.35, 0.2≤b≤0.4, 0.2≤c≤0.4, a+b+c=1, 0.8≤x / (a+b+c)≤1.08;
[0009] The chemical formula of P2-type layered sodium metal oxide is: Na X MnO y , 0.7≤x≤0.75, 0.2≤y≤0.25, in the XRD spectrum of the hybrid sodium ion battery positive electrode material, the relationship between the (002) crystal plane diffraction peak intensity I(002) and the (104) crystal plane diffraction peak intensity I(104) satisfies the following: 0.21 <I(002) / I(104)<0.27。
[0010] Furthermore, in the hybrid sodium ion battery positive electrode material, the mass percentage of O3-type layered sodium metal oxide in the hybrid sodium ion battery positive electrode material is 93%-91%, and the mass percentage of P2-type layered sodium metal oxide in the hybrid sodium ion battery positive electrode material is 7%-9%.
[0011] Preferably, in the hybrid sodium ion battery positive electrode material, the mass percentage of O3-type layered sodium metal oxide in the hybrid sodium ion battery positive electrode material is 90%-95%, and the mass percentage of P2-type layered sodium metal oxide in the hybrid sodium ion battery positive electrode material is 5%-10%.
[0012] Furthermore, in the XRD spectrum of the hybrid sodium ion battery positive electrode material, the diffraction angle 2θ1 of the (002) crystal plane is 15-17°, the diffraction angle 2θ2 of the (102) crystal plane is 39-40°, the diffraction angle 2θ3 of the (104) crystal plane is 49-50°, and the diffraction angle 2θ,4 of the (106) crystal plane is 62-63°.
[0013] Furthermore, in the XRD spectrum of the hybrid sodium ion battery positive electrode material, the (002) crystal plane diffraction peak intensity I(002) is 2000-2500 a.u., and the (104) crystal plane diffraction peak intensity I(104) is 9000-9800 a.u.
[0014] The present invention also provides a method for preparing any of the above-mentioned hybrid sodium ion battery positive electrode materials, characterized in that it comprises the following steps:
[0015] Step S1: Mix the nickel source, manganese source, iron source and sodium source and calcine them once;
[0016] Step S2: placing the calcined material in moist air with a humidity of 55% to 75%;
[0017] Step S3: adding a manganese source to the set aside material, and performing secondary calcination to obtain a hybrid sodium ion battery positive electrode material.
[0018] Furthermore, in step S1, the molar ratio of the metal elements in the sodium source, nickel source, iron source and manganese source is 0.75-1.05: 0.2-0.35: 0.2-0.4: 0.2-0.4, preferably: 0.9-1.0: 0.28-0.33: 0.30-0.35: 0.30-0.40.
[0019] Furthermore, the mass of manganese in the manganese source added in step S2 accounts for 2%-15% of the mass of the material after being shelved, preferably 8%-12%.
[0020] Furthermore, the temperature of the first calcination is 800-1050°C, preferably 900-980°C, and the time is 6-20h, preferably 8-12h; the temperature of the second calcination is 400-900°C, preferably 600-850°C, and the time is 5-12h, preferably 8-10h.
[0021] Furthermore, the storage time in the humid air is 12-36 hours, preferably 22-26 hours.
[0022] Furthermore, the sodium source used in step S1 is sodium carbonate, the nickel source is selected from one or more of nickel oxide and nickelous oxide, and the iron source is ferric oxide; the manganese source used in step S1 or step S3 is selected from one or more of manganese oxide, manganese dioxide, manganese trioxide and manganese tetraoxide.
[0023] The present invention also provides a sodium ion battery, comprising any of the above-mentioned hybrid sodium ion battery positive electrode materials or a hybrid sodium ion battery positive electrode material prepared by any of the above-mentioned methods for preparing the hybrid sodium ion battery positive electrode material.
[0024] In the present invention, the battery is prepared by conventional methods in the art, such as a sodium ion battery, including a positive electrode, a negative electrode, and an electrolyte. The positive electrode is prepared according to conventional techniques in the art, for example, the positive electrode material, the conductive agent and the binder of the present invention are prepared into a slurry, and coated on the surface of the current collector to form an electrode sheet. The content of the positive electrode material is 90-98wt%, the content of the conductive agent can be 0.2-6wt%, and the content of the binder is 0.2-6wt%. The conductive agent can be a conventional conductive agent, such as SP (carbon black conductive agent), SWCNT (single-walled carbon nanotube), etc. The binder can be a conventional binder, such as vinylidene fluoride PVDF, the solvent can be a conventional solvent, such as N-methylpyrrolidone NMP, and the current collector is a conventional current collector, such as aluminum foil. The negative electrode can use a conventional metal sodium sheet. The electrode liquid of the present invention can use a conventional commercially available sodium ion electrolyte, or it can be made by itself using existing conventional materials, for example, an electrolyte including a solvent and a sodium salt can be used, and the solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate. The sodium salt is selected from sodium hexafluorophosphate and / or sodium tetrafluoroborate.
[0025] The technical solution of the present invention has the following advantages:
[0026] 1. The hybrid sodium ion battery positive electrode material provided by the present invention comprises an O3 type layered sodium metal oxide and a P2 type layered sodium metal oxide coated on the surface of the O3 type layered sodium metal oxide; wherein the chemical formula of the O3 type layered sodium metal oxide is: Na x Ni a Fe b Mn c O2, 0.2≤a≤0.35, 0.2≤b≤0.4, 0.2≤c≤0.4, a+b+c=1, 0.8≤x / (a+b+c)≤1.08; The chemical formula of P2-type layered sodium metal oxide is: Na 0.7 MnO 2.05, in the XRD pattern of the positive electrode material of the hybrid sodium-ion battery, the relationship between the diffraction peak intensity I(002) of the (002) crystal plane and the diffraction peak intensity I(104) of the (104) crystal plane satisfies the following: 0.21 < I(002) / I(104) < 0.27.
[0027] By adding a P2-type positive electrode material protective layer on the surface of the O3-type sodium battery positive electrode material, the advantages of the two materials can be effectively combined (the high sodium content and high capacity of the O3-type positive electrode material; the stability of the P2-type positive electrode material), and the deficiencies between the two can be made up for (the air stability of the O3-type positive electrode material is poor, and sodium elements are easily precipitated in humid air; the sodium content of the P2-type positive electrode material is relatively low, so it is usually slightly lower). At the same time, compared with the traditional transition metal oxide coating, the P2-type positive electrode material has higher conductivity. Therefore, using a stable positive electrode material coating can basically not change the conductivity of the positive electrode material, and can effectively increase the air exposure stability of the material and reduce the surface residual alkali content.
[0028] For the positive electrode material of the hybrid sodium-ion battery, due to the differences in the synthesis process and conditions, the distribution of sodium and transition metal elements will be incomplete and uneven, which will seriously affect its stability. The diffraction peak of the (002) crystal plane represents the characteristic peak of the P2-type positive electrode material, and the diffraction peak of the (104) crystal plane represents the characteristic peak of the O3-type positive electrode material. I(002) / I(104) represents the coexistence of the P2-type positive electrode material and the O3-type positive electrode material to a certain extent, and the content of the P2-type positive electrode material is less than that of the O3-type positive electrode material. Therefore, the distribution uniformity of the O3-type positive electrode material is still the main body of the material. To ensure the stability of the positive electrode active material, the relationship between I(002) and I(104) is restricted: 0.21 < I(002) / I(104) < 0.27, so that the residual alkali on the surface of the positive electrode material of the hybrid sodium-ion battery is significantly reduced, and the stability exposed to air is improved, and the change rate of the surface residual alkali content before and after placement is reduced.
[0029] 2. The positive electrode material of the hybrid sodium-ion battery provided by the present invention can stably exist in a humid environment. After the mixed-phase treatment, it not only does not reduce the electrical performance of the material, but is also beneficial to improving the cycle stability of the material and the diffusion of sodium ions in the material.
[0030] 3. The preparation method of the hybrid sodium ion battery positive electrode material provided by the present invention comprises the following steps: mixing a nickel source, a manganese source, an iron source and a sodium source and calcining them once; placing the material after the primary calcination in humid air with a humidity of 55%-75%; adding a manganese source to the material after the placement, calcining it twice, and obtaining a hybrid sodium ion battery positive electrode material. In the hybrid sodium ion battery positive electrode material obtained by the above method, the mass content of O3-type layered sodium metal oxide and P2-type layered sodium metal oxide is appropriate, and the obtained positive electrode material can better improve the stability of the positive electrode material, reduce the change rate of the residual alkali content before and after exposure, and has a higher discharge specific capacity and better cycle stability.
[0031] 4. In the preparation method of the hybrid sodium ion battery positive electrode material provided by the present invention, when the mass of manganese in the manganese source added in step S2 accounts for 2%-15% of the mass of the material after being shelved, especially 8%-12%, and the shelving time in humid air is 12-36h, especially 22-26h, the obtained positive electrode material can better improve the stability of the positive electrode material, reduce the change rate of the residual alkali content before and after exposure, and have a higher discharge specific capacity and better cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 The positive electrode material of Example 1 of the present invention and Na 0.7 MnO 2.05 XRD diagram, the upper curve is the positive electrode material of Example 1, and the standard card is Na 0.7 MnO 2.05 . DETAILED DESCRIPTION
[0034] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0035] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0036] Example 1
[0037] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0038] (1) In a dry environment, nickel oxide, manganese oxide, iron oxide, and sodium carbonate are weighed and mixed in a beaker, wherein the molar ratio of each element is sodium: nickel: iron: manganese = 0.95: 0.30: 0.30: 0.40; the mixed material is calcined once; the calcination temperature is 930° C. and the time is 11 h.
[0039] (2) The calcined material is placed in moist air with a humidity of 65% for 24 hours;
[0040] (3) 15 g of manganese dioxide was added to 100 g of the material after being set aside, and the mixture was subjected to a secondary calcination treatment at a temperature of 720° C. for 8 h to obtain the final positive electrode material.
[0041] from Figure 1 It can be seen that the sodium ion battery positive electrode material of the present invention has diffraction peaks at 2θ angles of 15.8°, 32.1°, 39.7°, 50.0° and 62.7°. Among them, the diffraction angle 2θ1 of the (002) crystal plane is 15.8°, the diffraction angle 2θ2 of the (102) crystal plane is 39.7°, the diffraction angle 2θ3 of the (104) crystal plane is 50.0°, and the diffraction angle 2θ4 of the (106) crystal plane is 62.7°. Figure 1 It can be seen that the sodium ion battery positive electrode material of the present invention contains Na 0.7 MnO 2.05 .
[0042] Example 2
[0043] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0044] (1) In a dry environment, nickelous oxide, manganese oxide, iron oxide, and sodium carbonate are weighed and mixed in a beaker, wherein the molar ratio of each element is sodium: nickel: iron: manganese = 1.0: 0.28: 0.35: 0.30; the mixed material is calcined at a temperature of 900° C. for 12 h.
[0045] (2) The calcined material was placed in moist air with a humidity of 70% for 22 hours;
[0046] (3) 15 g of manganese dioxide was added to 100 g of the material after being set aside, and the mixture was calcined at 800° C. for 10 h to obtain the final positive electrode material.
[0047] Example 3
[0048] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, which is basically the same as that of Example 1, except that the holding time in step (2) is 36 hours.
[0049] Example 4
[0050] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, which is basically the same as that of Example 1, except that the holding time in step (2) is 12 hours.
[0051] Example 5
[0052] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, which is basically the same as Example 1, except that in step (3), the amount of manganese dioxide added is 23.7 g, and the proportion of Mn is 15%, wherein the proportion of Mn is the mass percentage of the manganese element to the mass percentage of the material after being set aside.
[0053] Example 6
[0054] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, which is basically the same as Example 1, except that in step (3), the amount of manganese dioxide added is 3.2 g, and the proportion of Mn is 2%.
[0055] Comparative Example 1
[0056] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, which is basically the same as that of Example 1, except that the shelving treatment in step (2) is not performed, but manganese dioxide is added to the material after the primary calcination and mixed, and then a secondary calcination is performed.
[0057] Comparative Example 2
[0058] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, which is basically the same as that of Example 1, except that manganese dioxide is not added to the material after being set aside in step (3) but a secondary calcination is directly performed.
[0059] Experimental Example 1
[0060] XRD test was performed on the sodium ion battery positive electrode materials prepared in each embodiment and comparative example. The (002) crystal plane diffraction peak intensity I(002) and the (104) crystal plane diffraction peak intensity I(104) are shown in the following table:
[0061]
[0062] It can be seen from the above table that Comparative Example 2 cannot form P2 type layered sodium metal oxide because manganese dioxide is not added. Comparative Example 1 has a low content of P2 type layered sodium metal oxide because it is not placed in a humid environment. Therefore, the (002) crystal plane diffraction peak intensity is low. Examples 1-6 of the present invention form a P2 type positive electrode material protective layer on the surface of the O3 type sodium battery positive electrode material, and the content of the P2 type positive electrode material protective layer is higher than that of Comparative Example 1.
[0063] Experimental Example 2
[0064] The molecular formula and content of the P2-type layered sodium metal oxide and the molecular formula and content of the O3-type layered sodium metal oxide in the sodium ion battery positive electrode material prepared in each embodiment and comparative example were determined.
[0065] The determination method of the molecular formula of the two types of sodium metal oxides is as follows: the molecular formula of the P2-type layered oxide is mainly determined by XRD testing, and the O3-type positive electrode material is mainly determined by the proportion of nickel, manganese, iron, and sodium sources in the first calcination and the sodium element precipitated after the first calcination is completed.
[0066] The contents of P2 type layered sodium metal oxide and O3 type layered sodium metal oxide in the positive electrode material of the sodium ion battery are calculated by the following method: Taking Example 1 as an example, the residual alkali content in 100g of the material after being set aside is determined, and the content of sodium (free sodium) precipitated on the surface of the material after being set aside is calculated according to the residual alkali content. The free sodium content is the sum of the sodium content in sodium carbonate and the sodium content in sodium hydroxide. The content of P2 type layered sodium metal oxide is calculated according to the free sodium content and the molecular formula of the P2 type positive electrode material. The content of O3 type layered sodium metal oxide is obtained by subtracting the content of P2 type layered sodium metal oxide from 100%.
[0067]
[0068] Experimental Example 3
[0069] The residual alkali content on the surface of the positive electrode materials prepared in each embodiment and comparative example was tested by an electrochemical titration method. After each group of positive electrode materials was exposed to the air for 3 days, the residual alkali content on the surface was tested again. The testing method for the residual alkali content was as follows: 1M hydrochloric acid solution was used as a titrant, 10g of the material to be tested was dissolved in 100ml of deionized water, and after the dissolution was completed, it was filtered, and 10g of the supernatant was taken for electrochemical titration. When two titration inflection points were displayed together, the titration was considered to be completed, and the change rate of the residual alkali content before and after exposure was calculated.
[0070] Residual alkali content before exposure (%) Residual alkali content after exposure / % Change rate / % Example 1 0.76 0.81 6% Example 2 0.82 0.87 6% Example 3 1.3 1.5 15% Example 4 1.1 1.3 18% Example 5 1.0 1.2 20% Example 6 1.2 1.5 25% Comparative Example 1 1.8 2.5 39% Comparative Example 2 8 12.8 60%
[0071] Compared with Comparative Examples 1-2, the positive electrode material obtained in the present invention can not only significantly reduce the residual alkali content before exposure, but more importantly, it can improve the stability of the positive electrode material and reduce the change rate of the residual alkali content before and after exposure.
[0072] Experimental Example 4
[0073] The sodium ion battery positive electrode material prepared in each embodiment and comparative example is used as a positive electrode active material to make a battery, comprising the following steps:
[0074] 1. Take the sodium ion battery positive electrode materials prepared in each embodiment and comparative example respectively, and mix them evenly in a degassing machine according to the mass ratio of positive electrode material, binder (polyvinylidene fluoride) and conductive agent (conductive carbon black) of 92:4:4, add NMP and mix well to obtain slurry, and coat it on aluminum foil with a surface density of 9 mg / cm 2 , get the positive electrode, and then perform buckle assembly.
[0075] 2. Button assembly: Assemble the positive electrode shell (304 stainless steel) - spring (304 stainless steel) - gasket (304 stainless steel) - positive electrode (aluminum foil coated with positive electrode material) - diaphragm (PE) - electrolyte (containing 1 mol / L sodium hexafluorophosphate, the solvent is EC (ethylene carbonate): DEC (diethyl carbonate) with a volume ratio of 3:7) - negative electrode (sodium sheet) - negative electrode shell (304 stainless steel) in this order to obtain a sodium ion battery.
[0076] 3. Take the sodium ion batteries prepared in each embodiment and comparative example at room temperature, 0.1C discharge specific capacity, 50-week capacity retention rate (the specific method is, at room temperature, 0.1C is charged to 4.05V, 0.1C is discharged to 2V, then 1C is charged to 4.05V, 1C is discharged to 2V, 1C is charged to 100V, 1C is charged to 2V, 1C is charged and discharged 50 times, and the capacity retention rate data is obtained.
[0077] project First discharge specific capacity (mAh / g) Capacity retention rate / % Example 1 153 98.6 Example 2 155 97.9 Example 3 149 96.1 Example 4 146 95.6 Example 5 146 96.6 Example 6 147 95.8 Comparative Example 1 136 93.3 Comparative Example 2 127 90.3
[0078] Compared with Comparative Examples 1-2, the discharge specific capacity and cycle stability of the sodium battery made from the positive electrode material of the present invention are significantly improved.
[0079] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A hybrid sodium ion battery positive electrode material, characterized in that: It includes O3 type layered sodium metal oxide and P2 type layered sodium metal oxide coated on the surface of O3 type layered sodium metal oxide; Among them, the chemical formula of O3 type layered sodium metal oxide is: Na x Ni a Fe b Mn c O2, 0.2≤a≤0.35, 0.2≤b≤0.4, 0.2≤c≤0.4, a+b+c=1, 0.8≤x / (a+b+c)≤1.08; The chemical formula of P2-type layered sodium metal oxide is: Na X MnO y , 0.7≤x≤0.75, 0.2≤y≤0.25, in the XRD spectrum of the hybrid sodium ion battery positive electrode material, the relationship between the (002) crystal plane diffraction peak intensity I(002) and the (104) crystal plane diffraction peak intensity I(104) satisfies the following: 0.21 <I(002) / I(104)<0.27。 2. The hybrid sodium ion battery positive electrode material according to claim 1, characterized in that: In the hybrid sodium ion battery positive electrode material, the mass percentage of O3-type layered sodium metal oxide in the hybrid sodium ion battery positive electrode material is 90%-95%, and the mass percentage of P2-type layered sodium metal oxide in the hybrid sodium ion battery positive electrode material is 5%-10%.
3. The hybrid sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: In the XRD spectrum of the hybrid sodium ion battery positive electrode material, the diffraction angle 2θ1 of the (002) crystal plane is 15-17°, the diffraction angle 2θ2 of the (102) crystal plane is 39-40°, the diffraction angle 2θ3 of the (104) crystal plane is 49-50°, and the diffraction angle 2θ,4 of the (106) crystal plane is 62-63°; and / or, in the XRD spectrum of the hybrid sodium ion battery positive electrode material, the diffraction peak intensity I(002) of the (002) crystal plane is 2000-2500 a.u., and the diffraction peak intensity I(104) of the (104) crystal plane is 9000-9800 a.u.
4. A method for preparing a hybrid sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: Step S1: mixing the nickel source, manganese source, iron source and sodium source and calcining them once; Step S2: placing the calcined material in moist air with a humidity of 55% to 75%; Step S3: adding a manganese source to the set aside material, and performing secondary calcination to obtain a hybrid sodium ion battery positive electrode material.
5. The method for preparing a hybrid sodium ion battery positive electrode material according to claim 4, characterized in that: In step S1, the molar ratio of the metal elements in the sodium source, the nickel source, the iron source and the manganese source is 0.75-1.05: 0.2-0.35: 0.2-0.4: 0.2-0.
4.
6. The method for preparing a hybrid sodium ion battery positive electrode material according to claim 5, characterized in that: In step S1, the molar ratio of the metal elements in the sodium source, the nickel source, the iron source, and the manganese source is 0.9-1.0: 0.28-0.33: 0.30-0.35: 0.30-0.
40.
7. The method for preparing a hybrid sodium ion battery positive electrode material according to claim 4, characterized in that: The mass of manganese in the manganese source added in step S2 accounts for 2%-15% of the mass of the material after being shelved.
8. The method for preparing a hybrid sodium ion battery positive electrode material according to claim 7, characterized in that: The mass of manganese in the manganese source added in step S2 accounts for 8%-12% of the mass of the material after being shelved.
9. The method for preparing a hybrid sodium ion battery positive electrode material according to any one of claims 4 to 8, characterized in that: The sodium source used in step S1 is sodium carbonate, the nickel source is selected from one or more of nickel oxide and nickelous oxide, and the iron source is ferric oxide; the manganese source used in step S1 or step S3 is selected from one or more of manganese oxide, manganese dioxide, manganese trioxide and manganese tetraoxide.
10. The method for preparing a hybrid sodium ion battery positive electrode material according to any one of claims 4 to 8, characterized in that: The temperature of the first calcination is 800-1050°C, and the time is 6-20h; the temperature of the second calcination is 400-900°C, and the time is 5-12h.
11. The method for preparing a hybrid sodium ion battery positive electrode material according to claim 10, characterized in that: The temperature of the first calcination is 900-980°C and the time is 8-12h; the temperature of the second calcination is 600-850°C and the time is 8-10h.
12. The method for preparing a hybrid sodium ion battery positive electrode material according to any one of claims 4 to 8, characterized in that: The shelf time in humid air is 12-36h.
13. The method for preparing a hybrid sodium ion battery positive electrode material according to claim 12, characterized in that: The shelf time in humid air is 22-26h.
14. A sodium ion battery, characterized in that: A hybrid sodium ion battery positive electrode material comprising the hybrid sodium ion battery positive electrode material described in any one of claims 1 to 3 or a hybrid sodium ion battery positive electrode material prepared by the preparation method of the hybrid sodium ion battery positive electrode material described in any one of claims 4 to 13.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN114744179A
O3-P2 composite phase sodium ion positive electrode material as well as preparation method and application thereof
CN115148984A
Composite positive electrode material and preparation method thereof
CN113991079A
Layered active materials for sodium ion batteries
CN114207878A